Activation of Coagulation and Fibrinolysis in Acute Respiratory Distress Syndrome: A Prospective Pilot Study - Ozolina, Agnese; Sarkele, Marina; Sabelnikovs, Olegs; Skesters, Andrejs; Jaunalksne, Inta; Serova, Jelena; Ievins, Talis; Bjertnaes, Lars J.; Vanags, Indulis (Frontiers in Medicine, 2016)
Introduction: Coagulation and fibrinolysis remain sparsely addressed with regards to acute respiratory distress syndrome (ARDS). We hypothesized that ARDS development might be associated with changes in plasma coagulation and fibrinolysis. Our aim was to investigate the relationships between ARDS diagnosis and plasma concentrations of tissue factor (TF), tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) in mechanically ventilated patients at increased risk of developing ARDS. Materials and Methods: We performed an ethically approved prospective observational pilot study. Inclusion criteria: patients with PaO2/FiO2 < 300 mmHg admitted to the intensive care unit (ICU) for mechanical ventilation for 24 hours, or more, because of one or more disease conditions associated with increased risk of developing ARDS. Exclusion criteria: age below 18 years; cardiac disease. We sampled plasma prospectively and compared patients who developed ARDS with those who did not using descriptive statistics and chi-square analysis of baseline demographical and clinical data. We also analyzed plasma concentrations of TF, t-PA and PAI-1 at inclusion (T0) and on third (T3) and seventh day (T7) of the ICU stay with non-parametric statistics inclusive their sensitivity and specificity associated with the development of ARDS using receiver operating characteristic (ROC) curve analysis. Statistical significance: p < 0.05. Results: Of 24 patients at risk, six developed mild ARDS and four of each moderate or severe ARDS, respectively, 3 ± 2 (Mean ± SD) days after inclusion. Median plasma concentrations of TF and PAI-1 were significantly higher at T7 in patients with ARDS, as compared to non-ARDS. Simultaneously, we found moderate correlations between plasma concentrations of TF and PAI-1, TF and PaO2/FiO2 and PEEP and TF. TF plasma concentration was associated with ARDS with 71% sensitivity and 100% specificity, a cut off level of 145 pg/ml and AUC 0.78, p = 0.02. PAI-1 displayed 64% sensitivity and 100% specificity with a cut off concentration of 117.5 pg/ml and AUC 0.77, p = 0.02. t-PA did not change significantly during the observation time. Conclusions: This pilot study showed that increased plasma concentrations of TF and PAI-1 might support ARDS diagnoses in mechanically ventilated patients after seven days in ICU.